Implementasi Teknologi IOT Untuk Pengontrolan Peralatan Elektronik Rumah Tangga Berbasis Android - Arya Daiva Maulana; Aji Setiawan (Journal TIFDA (Technology Information and Data Analytic), 2025)
The development of information technology has triggered innovation in various sectors, one of which is the Internet of Things (IoT). This study aims to develop a prototype controller for Android-based electronic devices using IoT technology. The method used involves object-focused techniques and uses Wookwi as the main tool. This prototype utilizes an internet connection to allow users to control electronic devices such as lights and others remotely. The user interface is presented through the Blynk platform. In this context, the study highlights the difficulty of controlling several electronic devices with a remote control separately. The implementation of IoT in controlling electronic devices at home is expected to overcome these obstacles. This study proposes the development of a system that uses an internet connection to control electronic devices, especially through smartphones. This not only increases user convenience but also helps reduce energy waste and high electricity costs. The research involves the stages of data collection, analysis, and system design with a focus on the use of the Blynk microcontroller, which acts as the brain in the control system. The result is a prototype application that allows users to control electronic devices efficiently via the internet, providing a practical solution to overcome challenges in remote control. In conclusion, the implementation of IoT in this prototype proves that users can easily control electronic devices remotely, increasing the efficiency of electrical energy use.